Narratives of sex workers: intimate partner violence and coping strategies - Milena Oliveira Costa; Valéria Cristina Christello Coimbra; Michele Mandagará de Oliveira; Clarissa de Souza Cardoso; Vania Dias Cruz; Ariane da Cruz Guedes; Josiane da Costa Moreira; Luciano Santos Gentilini (Revista Brasileira de Enfermagem)
ABSTRACT Objectives: to understand the narratives of sex workers about violence suffered by intimate partners and their coping strategies. Methods: qualitative research, focused on thematic oral history, carried out with six sex workers in southern Brazil, who responded to in-depth interviews using a flexible script. Thematic content analysis was used. Results: the study included cisgender women who self-identified as half black and half white. Most had children and were separated. They reported abusive relationships by their intimate partners, with emphasis on verbal, psychological, financial, and physical violence and attempted femicide. Such violence resulted in coping strategies, such as avoiding emotional bonds and maintaining a discreet life. Final Considerations: intimate partner violence is prevalent among participants, leading them to adopt strategies to preserve their safety and well-being, highlighting the need for public policies that meet their particularities and guarantee protection.